PSECO-IM: An Approach for Incident Management to Support Governance in Proprietary Software Ecosystems - Costa, Luiz Alexandre; Fontão, Awdren; Santos, Rodrigo (Anais Estendidos do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2022)
A proprietary software ecosystem (SECO) concerns data concentrated on a technological platform with contributions protected by intellectual property. The platform that supports the business initiatives is developed using different technologies with integration points, promoting a network of dependencies and architectural complexities. Systems downtime (incidents) causes major image and financial upheavals for organizations. To mitigate the risks of incidents, the IT management team should implement strategies based on governance mechanisms to sustain the platform. This work aims to develop and evaluate a process-based approach (PSECO-IM) for incident management to support the IT management team in governing a technology platform architecture in a proprietary SECO. This work is based on Work System Theory (WSF), in which the systems in organizations should be seen as work systems and technologies as components of work systems. As a final result, we got positive feedback on the relevance of our proposal from the organization’s practitioners, such as: i) mitigating the opening of incidents; ii) measuring the health of the proprietary SECO through new metrics and indicators; and iii) discovering patterns in software projects that may represent a chance of opening incidents. We argue that this work contributes to the Information Systems area since it covers studies on three pillars: people, process, and technology, such as tacit knowledge, low-quality software, governance, incident management, and proprietary SECO.